Integrating an Anti-Drug Curriculum into Character Education: A Qualitative Study on Students’ Moral Development in Public Senior High Schools - Eldawati; Rada; Suparta (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study investigates how an anti-drug curriculum can be systematically integrated into formal schooling to strengthen students’ moral and character development. It examines the processes, strategies, and impacts of embedding anti-drug education across multiple subjects in public senior high schools, positioning prevention not as an extracurricular activity but as part of daily instructional practices. The study seeks to understand how curriculum integration functions as a preventive mechanism to reduce adolescents’ vulnerability to drug misuse while fostering ethical awareness, self-regulation, and responsible behavior. A descriptive qualitative design with a field research orientation was employed. The research was conducted in two public senior high schools in Pangkalpinang that implemented the program in collaboration with the National Narcotics Agency. Participants included school leaders, subject teachers, and students selected through purposive sampling. Data were collected through participant observation, semi-structured interviews, and document analysis. Thematic analysis was applied using iterative coding, categorization, and interpretation, while trustworthiness was ensured through triangulation, member checking, and audit trails. The findings reveal three interconnected stages of implementation: institutional preparation, collaborative curriculum planning, and classroom-based integration. Integrating anti-drug content into Islamic Education, Civics, Science, and Physical Education enhanced students’ knowledge of drug risks, strengthened moral values, and developed life skills such as assertiveness, self-control, and resistance to peer pressure. Although challenges related to time constraints and limited parental involvement remain, the program contributed to improved character formation and healthier behavioral tendencies. This study offers originality by presenting a curriculum-based prevention model embedded within everyday teaching rather than short-term campaigns. It contributes theoretically to interdisciplinary character education and practically provides a replicable framework for schools and policymakers seeking sustainable strategies to address adolescent risk behaviors.